Modulation of allergic airways disease employing bio-mimetic nanoparticles with TLR agonists - Scalise, Melanie Cristine; Mutlu, Seyran; Ferrié, Céline; Amacker, Mario; von Garnier, Christophe; Stumbles, Philip; Blank, Fabian (Frontiers in Allergy, 2025)
IntroductionAllergic asthma is characterized by airway hyperresponsiveness due to a biased Th2 immune response against harmless environmental substances. While most current treatments alleviate symptoms without altering the disease's progression, allergen-specific immunotherapy (AIT) is the only clinically approved strategy known to modify the natural course of allergic disease. However, AIT has limitations, highlighting the need for improved formulations that provide safer, faster, and more effective immune modulation.MethodsIn this study, we designed bio-mimetic nanoparticles and evaluated their effects in a mouse model of experimental allergic inflammatory airways disease (EAIAD). Mice were sensitized with ovalbumin (OVA) and treated with liposomes or virosomes conjugated with OVA and the TLR7/8 agonist 3M-052. Lung function, inflammatory cell recruitment, cytokine profiles, and immunoglobulin levels were analyzed post-treatment.ResultsAmong the tested formulations, liposomes co-delivering OVA and 3M-052 (Lipo-OVA) led to partial improvements in lung mechanics, including lower airway resistance (Rrs) and preserved forced expiratory volume (FEV0.1). Immune profiling revealed formulation-specific effects on eosinophil and macrophage populations, and modest shifts in cytokine secretion patterns. However, no formulation fully resolved airway inflammation or significantly reduced Th2 cytokines or total IgE levels.DiscussionThese findings support the feasibility of nanoparticle-based AIT strategies, while also highlighting the need for further optimization to enhance efficacy, minimize sensitization, and promote sustained long-term immune tolerance.